Patterns of Gastrointestinal Helminth Infections in Rattus rattus, Rattus norvegicus, and Mus musculus in Chile - Grandón-Ojeda, Alexandra; Moreno, Lucila; Garcés-Tapia, Carolina; Figueroa-Sandoval, Fernanda; Beltrán-Venegas, Jazmín; Serrano-Reyes, Josselyn; Bustamante-Garrido, Bárbara; Lobos-Chávez, Felipe; Espinoza-Rojas, Hellen; Silva-de la Fuente, María Carolina; Henríquez, AnaLía; Landaeta-Aqueveque, Carlos (Frontiers in Veterinary Science, 2022)
Few studies have assessed the patterns of parasite populations of rodents over a longitudinal gradient in Chile. In this work, the gastrointestinal helminthic fauna of invasive rodents in Chile was examined to assess the association between their presence/absence and abundance with latitude, host sex, and host body condition, and to assess the coexistence and correlation of the abundance between parasite species. Rodents were obtained from 20 localities between 33 and 43°S. Helminths were extracted from the gastrointestinal tract and identified morphologically. Overall, 13 helminth taxa were obtained. The most frequently identified parasite species was Heterakis spumosa, and the most abundant was Syphacia muris, while Physaloptera sp. was the most widely distributed. No locality presented with a coexistence that was different from that expected by chance, while the abundance of five helminthic species correlated with the abundance of another in at least one locality, most likely due to co-infection rather than interaction. Host sex was associated with parasite presence or abundance, and female sex-biased parasitism was notably observed in all cases. Body condition and latitude presented either a positive or negative association with the presence or abundance of parasites depending on the species. It is notable that the likely native Physaloptera sp. is widely distributed among invasive rodents. Further, gravid females were found, suggesting spillback of this species to the native fauna. The low frequency and abundance of highly zoonotic hymenolepid species suggest that rodents are of low concern regarding gastrointestinal zoonotic helminths.